Assessing the effect of carbon dioxide emissions on agricultural production in Nigeria (2010-2023) - Effiong, Mfonobong Okokon; Panicker, Manoj (Edelweiss Applied Science and Technology, 2025)
This study examines the relationship between carbon dioxide equivalent (CO2e) emissions and agricultural production (food, livestock, cereals, and crops) in Nigeria from 2000 to 2023, with a focus on trend analysis, long-run dynamics (Vector Error Correction Model - VECM), and short-run dynamics (Vector Autoregression - VAR). The study employs a quantitative approach, utilizing secondary data from the World Development Indicators (WDI) database. The trend analysis revealed a widening gap between CO2e emissions and food production, indicating a potential threat to food security. Results indicated a significant positive relationship between CO2e emissions and agricultural production at a 1% significance level, with coefficients of 0.937, 0.944, 0.957, and 0.519 for food, crop, cereals, and livestock production, respectively. Additionally, findings showed that a 1% increase in livestock and cereal production decreases CO2e emissions by 0.668% (p-value=0.040) and 77.99% (p-value=0.019), respectively. The results suggest a CO2 fertilization effect, particularly for food (t-stat=2.393, p-value=0.05) and cereals production (t-stat=4.284, p-value=0.05). Although contradicting general expectations that emissions would negatively impact agricultural productivity, these findings contribute significantly to the literature on climate change and agriculture, emphasizing the need for sustainable agricultural practices, climate-resilient crop varieties, and environmentally friendly incentives to mitigate climate change impacts on agricultural production.